2007
DOI: 10.1007/s00449-007-0171-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on enzymatic acylation of konjac glucomannan

Abstract: A comparative study was made of enzymatic acylation of konjac glucomannan with vinyl esters under ultrasonic irradiation and shaking in organic solvent tert-butanol. Among the 13 enzymes selected, Novozym 435 exhibited the highest acylation activity towards KGM whether under ultrasonic irradiation or shaking. The application of ultrasonic irradiation instead of shaking during the acylation led to improvement in the initial reaction rate, yield and degree of substitution of the modified KGM. Appropriate ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Xiao et al [55] and Chen et al [56] found that the ultrasound did not amend the regioselectivity of lipase. Other authors also observed the positive effects of ultrasound in lipase-catalyzes reactions [53,57]. Several other authors have postulated that enzymatic activity in non-aqueous solvents may be diminished due to diffusional limitations on the substrates.…”
Section: Effect Of Ultrasound On Lipase Activitymentioning
confidence: 92%
“…Xiao et al [55] and Chen et al [56] found that the ultrasound did not amend the regioselectivity of lipase. Other authors also observed the positive effects of ultrasound in lipase-catalyzes reactions [53,57]. Several other authors have postulated that enzymatic activity in non-aqueous solvents may be diminished due to diffusional limitations on the substrates.…”
Section: Effect Of Ultrasound On Lipase Activitymentioning
confidence: 92%
“…Much recent work has examined ultrasonically enhanced enzymatic synthesis in organic solvents with small amounts of water added to generate a two-phase system. Thus, acylation, this time of konjac glucomannan (KGM; a skin conditioner and a natural thickener obtained from the Asiatic tuber Amorphophallus konjac ), has been reported (Chen et al, 2008b) and is compared with just shaking in tertiary-butanol as solvent. Of the 13 enzymes studied, Novozym 435 showed the best activity on KGM whether with ultrasound or shaking, though the former produced the best improvement in the initial reaction rate, yield and degree of substitution when 100 W power and some added water were studied.…”
Section: Use Of Ultrasonically Stimulated Enzymes In Synthesismentioning
confidence: 99%
“…In general, in these reactions US did not change the regioselectivity of the enzymatic acylation (Xiao et al, 2005;Chen et al, 2008).…”
Section: Enzymatic Synthesis Of Carbohydrate Derivativesmentioning
confidence: 83%
“…carried out the esterification of fructose with palmitate in IL under US (47 kHz, 185 W, 60 °C, 6 h) and the conversion was 78%, while the use of magnetic stirring only led to 62% esterification. Chen et al (2008) studied the effect of US on enzymatic acylation of konjac glucomannan (KGM) with vinyl esters in tert-butanol. The acylated forms of KGM have shown to be promising as a novel drug, an environmentally benign emulsifier, and as drug carriers.…”
Section: Enzymatic Synthesis Of Carbohydrate Derivativesmentioning
confidence: 99%